Comparative study on performance of basalt fiber asphalt concrete after environmental action. Issue 5 (March 2020) - Yan, Jingchen; Yan, Junjie; Zheng, Jianlong
Abstract: The AC-16 asphalt concrete with A grade 90# asphalt and A grade 90# asphalt mixed with 0.3% basalt fiber as the binder was taken as the research object, passing the rutting test, trabecular bending test and freeze-thaw splitting test. The high temperature stability, low temperature crack resistance and water stability of the two asphalt mixtures after different environmental impact factors showed that the dynamic stability, maximum bending strain and residual strength ratio of the basalt fiber reinforced asphalt concrete were significantly higher. In the matrix asphalt concrete. The dynamic stability of basalt fiber asphalt concrete compared with matrix asphalt concrete increased by 15.79%, 14.7%, 16.51%, 18.18%, respectively, after environmental influence factors and UV, high and low temperature alternating, freeze-thaw and salt freezing environment. 17.95%; after the same environmental action, the maximum bending strain of basalt fiber asphalt concrete increased by 14.99%, 30.57%, 18.77%, 19.29%, 15.94%, respectively; the residual strength ratio increased by 3.82%, 5.61%, 8.82%, 10.76%, 10.36%; and the accuracy of the test data was verified microscopically from the action of basalt fiber by scanning electron microscopy.